Analisis Pemberian Kredit Pada Program Kemitraan) PT. Telkom (Studi Pada Usaha Mikro Kecil dan Menengah (UMKM) Sektor Industri Binaan PT. Telkom Malang Regional V Jawa Timur - Intan Nuraini; Juni Herawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Since 2010, the growth rate of SMEs are increase significantly so it can decrease unemployment and is able to improve the Indonesian economy. However, there are some problems of SMEs there are capital, resources, promotion and raw materials. To respond to these problems, the government established the Corporate Social Responsibility (CSR) which is conducted by the State Owned Enterprises (SOEs), and it call as Partnership Program and Community Development that provide credit and assistance to SMEs in developing their business. This study aimed to examine the differences before and after crediting Partnership Program PT. Telkom Malang and sales turnover for the development of SMEs. Business development here projected by profitability of SMEs. The population was assisted partner SMEs PT. Telkom Malang in 2010-2013. Sampling technique is purposive sampling and obtained 7 SMEs for research samples. The analysis technique used is t test average difference and calculate the average profitability ratios such as the ratio of net profit margin (NPM) and Return On Investment (ROI). Confidence level (α) used in this study was 0.05. The results using the t test average difference indicates that there is a difference before and after the provision of credit and an increase in profitability of SMEs. The increase in this ratio indicate that lending Partnership effect on the development of SMEs.Keywords: Corporate Social Responsibilty, Partnership Program and Community Development, PT. Telekomunikasi Indonesia Tbk., Credit, Sales turnover, profitability, business development, Micro, Small and Medium Enterprises (SMEs).